Detection of faecal bacteria and antibiotic resistance genes in biofilms attached to plastics from human-impacted coastal areas. (15th February 2023) - Liang, Hongxia; de Haan, William P.; Cerdà-Domènech, Marc; Méndez, Javier; Lucena, Francisco; García-Aljaro, Cristina; Sanchez-Vidal, Anna; Ballesté, Elisenda
Abstract: Plastics have been proposed as vectors of bacteria as they act as a substrate for biofilms. In this study, we evaluated the abundance of faecal and marine bacteria and antibiotic resistance genes (ARGs) from biofilms adhered to marine plastics. Floating plastics and plastics from sediments were collected in coastal areas impacted by human faecal pollution in the northwestern Mediterranean Sea. Culture and/or molecular methods were used to quantify faecal indicators ( E. coli, Enterococci and crAssphage), and the ARGs sul I, tet W and bla TEM and the 16S rRNA were detected by qPCR assays. Pseudomonas and Vibrio species and heterotrophic marine bacteria were also analysed via culture-based methods. Results showed that, plastic particles covered by bacterial biofilms, primarily consisted of marine bacteria including Vibrio spp. Some floating plastics had a low concentration of viable E. coli and Enterococci (42% and 67% of the plastics respectively). Considering the median area of the plastics, we detected an average of 68 cfu E. coli per item, while a higher concentration of E. coli was detected on individual plastic items, when compared with 100 ml of the surrounding water. Using qPCR, we quantified higher values of faecal indicators which included inactive and dead microorganisms, detecting up to 2.6 × 10 2 gc mm −2 . The ARGs were detected in 67–88% of the floating plastics and in 29–57% of the sediment plastics with a concentration of up to 6.7 × 10 2 gc mm −2 . Furthermore, enrichment of these genes was observed in biofilms compared with the surrounding water. These results show that floating plastics act as a conduit for both the attachment and transport of faecal microorganisms. In contrast, low presence of faecal indicators was detected in plastic from seafloor sediments. Therefore, although in low concentrations, faecal bacteria, and potential pathogens, were identified in marine plastics, further suggesting plastics act as a reservoir of pathogens and ARGs. Graphical abstract: Image 1 Highlights: From 4.9x10⁴ to 8.7x10⁶ 16S rRNA gene gc mm -2 were detected on plastics. An average sized plastic item held from 9.1x10¹ to 1.1x10 4 cfu Vibrio spp. Faecal indicators were detected in plastics in faecally polluted areas. Higher concentration of E. coli was detected in a single plastic than in the water. Marine plastics were colonised by faecal bacteria and drifted to cleaner areas. There was an enrichment of faecal indicators and ARGs in the plastic biofilm.